2012 IEEE/RSJ International Conference on Intelligent Robots and Systems 2012
DOI: 10.1109/iros.2012.6385614
|View full text |Cite
|
Sign up to set email alerts
|

Contextual scene segmentation of driving behavior based on double articulation analyzer

Abstract: Various advanced driver assistance systems (ADASs) have recently been developed, such as Adaptive Cruise Control and Precrash Safety System. However, most ADASs can operate in only some driving situations because of the difficulty of recognizing contextual information. For closer cooperation between a driver and vehicle, the vehicle should recognize a wider range of situations, similar to that recognized by the driver, and assist the driver with appropriate timing.In this paper, we assumed a double articulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…It is also assumed that a boundary between two adjacent driving words represents a contextual changing point. These assumptions are supported by several previous studies [1], [3]- [5]. Fig.…”
Section: B Daa and Predictionsupporting
confidence: 87%
See 4 more Smart Citations
“…It is also assumed that a boundary between two adjacent driving words represents a contextual changing point. These assumptions are supported by several previous studies [1], [3]- [5]. Fig.…”
Section: B Daa and Predictionsupporting
confidence: 87%
“…Takenaka et al reported that the DAA was able to infer contextual changing points of driving-behavior data as boundaries of driving words [1]. 1 They used a sticky HDP-HMM for segmenting driving-behavior data and obtaining driving letter sequences.…”
Section: A Daa Using Hdp-hsmmmentioning
confidence: 99%
See 3 more Smart Citations